PENINGKATAN MINAT DAN HASIL BELAJAR TEKNOLOGI PERKANTORAN MELALUI PENERAPAN METODE PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFAE) - Sufriadi Sufriadi (Jurnal Guru Dikmen dan Diksus, 2022)
The background of this research is due to the low interest in learning of students which results in not maximal learning outcomes that they achieve, this study aims to increase interest and learning outcomes in Office Technology subjects for students in class X Office Automation and Governance (OTKP) SMKN 1 Sinjai, through the Student Facilitator and Explaining (SFAE) technique. The research was carried out in 2 (two) cycles, with stages : 1) planning, 2) observation, 3) implementation and 4) reflection. The research subjects were students of class X OTKP-1 SMKN 1 Sinjai. Data collection techniques for the cognitive domain are in the form of evaluation tests, for the affective and psychomotor domains, interest questionnaires and observation sheets are used. The results showed that there was an increase in the score with the average pretest interest in learning from the first cycle reaching 73 percent (medium category). Cycle II the average value of posttest interest in learning reached 77 percent classically (high category). For learning outcomes also increased, namely: the first cycle reached 80.77 percent. While in the second cycle it reached 96.15 percent. Then the affective domain in the first cycle reached an average value of 61.5 percent. Furthermore, in cycle II it reached 100 percent, meaning an increase of 38.5 percent. While in the psychomotor domain of cycle I the average value reached 61.54 percent. While the second cycle reached 100 percent. This shows that the interest and learning outcomes of students have increased by applying the SFAE learning method.